TEACHING SPEAKING BY COMBINING OF STICK PUPPET AND ROLE PLAY FOR THE EIGHTH GRADE STUDENTS - Tri Maulidasari; S Sumani; Brigitta Septarini (English Teaching Journal : A Journal of English Literature, Language and Education, 2017)
The aims of this research is to describe the implementation, problems and the solutions of problems in the teaching speaking by combining of stick puppet and role play for the eighth grade students of MTsN Kedungjati in the schooling year of 2016/2017. This research uses descriptive qualitative research. The participants of the research are the English teacher and students of VIIIB of MTsN Kedungjati. The techniques used to collect the data are observation, interview and documentation. While the technique of data analysis are data condensation, data display and conclusion  and verification. The result of the research are: (1). The implementation of teaching speaking by combining of stick puppet and role play divided into three steps, they are: pre activity ,Whilst activity , Post activity (2). The problems of the implementation of teaching speaking by combining of stick puppet and role play: The class becomes crowded,  the students are difficult to pronounce the words, and  some of the students do not master the script. (3). The solutions of the problems are the teacher asks the students to keep silent and pay attention the other groups, gives the evaluations and straighten of students’ mistakes  in pronunciation, the students are given enough time to memorize the script and bring the dictionary.